Proceso de atención de enfermería en paciente adulto con enfermedad de hodgkin - Jurado Burgos, Jonathan (2018)
Hodgkin's lymphoma is a pathology that attacks the immune system specifically to the lymphatic system being left without defenses and exposed to any viral disease so it becomes more complicated to treat it, diagnosing it early is very important to be able to treat this type of cancer. The process of nursing care is considered as a useful tool when carrying out our working day, allowing us to identify the problems that our patients face in order to provide them with comprehensive and meticulous care, improving their health and thus quality of life. Health professionals are obliged to have information about diseases that are not so common during our daily work, it is essential to have constant training in the nursing area to be able to treat this type of diseases which require specialized attention. The emotional and unconditional support of both the family and the health professional is essential for the favorable recovery of patients diagnosed with this type of carcinogenic diseases, because of their health condition it is vital that the nurse achieve not only restore their physical health but also his emotional state